Recent Patents on Greenhouse Cooling Techniques: A Review - Al-Ismaili, Abdulrahim M.; Al-Maimani, Asma M.; Al-Saadi, Aaisha K.; Al-Kindi, Fatma S.; Al-Manthri, Ibtihal A.; Al-Jabri, Khaled M.; Al-Dairi, Mai K.; Al-Mahroqi, Seham H. (Recent Patents on Engineering, 2021)
Background: Greenhouse cooling is very essential during warm conditions to extend the cropping season and offer year-round production. Although fan-pad systems are widely utilized for greenhouse cooling in arid climates, they have many drawbacks mentioned by researchers. Thus, finding the best cooling system had attracted the attention of many researchers and inventors in such climates. Objective: This paper aims to review the recent patents of greenhouse cooling methods suitable for arid climates. Methods: The most relating patents on greenhouse cooling technologies were discussed and analyzed. Results: A total of 46 patents were reviewed, covering over 21 years, and the majority of them (73.9%) were patented in China, followed by the USA (15.2%), worldwide (4.3%), Japan (2.2%), Russia (2.2%) and Austria (2.2%). The patents were divided into three categories; preventive (8 patents), corrective (33 patents) and combined (5 patents) greenhouse cooling techniques. In the preventive techniques, i.e. avoiding heat load in greenhouses, patents involving shading mechanisms were dominant because it is well known that shading reduces solar radiation penetration as the largest heating source in greenhouses. In the corrective techniques, i.e. removing the accumulated heat, patents on evaporative cooling mechanisms were dominant but their suitability for arid climates is hindered with high humidity and water scarcity. In the combined techniques, i.e. including both preventive and corrective techniques, patents are very comprehensive and thus implementable in hightech commercial greenhouses. Some innovative patents involving refrigerative cooling, desiccation, solar power and multi-systems were also highlighted. Conclusion: Patents implementing preventive cooling techniques alone are insufficient in arid climates due to the extremely high ambient temperatures in the hot months. Similarly, patents involving evaporative cooling methods are constrained by high humidity and water scarcity in arid conditions. Therefore, patents combining preventive and corrective techniques are more energy- and water- efficient. We recommend future work to focus on desiccant-indirect evaporative cooling methods as they can overcome the high humidity limitations in many arid areas.
Keywords: Greenhouse cooling